2012
DOI: 10.1002/biof.1012
|View full text |Cite
|
Sign up to set email alerts
|

Zinc in the central nervous system: From molecules to behavior

Abstract: The trace metal zinc is a biofactor that plays essential roles in the central nervous system across the lifespan from early neonatal brain development through the maintenance of brain function in adults. At the molecular level, zinc regulates gene expression through transcription factor activity and is responsible for the activity of dozens of key enzymes in neuronal metabolism. At the cellular level, zinc is a modulator of synaptic activity and neuronal plasticity in both development and adulthood. Given thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 83 publications
1
88
0
Order By: Relevance
“…The ZnT3 protein (encoded by the SLC30A3 gene) belongs to a class of proteins whose function is to lower the intracellular zinc concentrations, facilitating efflux of intracellular vesicles in the cytoplasm and/or extracellular spaces, and plays a particularly important role in neuronal zinc regulation. This protein is responsible for the accumulation of free zinc in glutamatecontaining vesicles found in the hippocampus and cortex (Gower-Winte and Levenson 2012). The SLC30A3 gene is expressed in brain regions important for cognitive development and development of different kinds of memory, such as the hippocampus, cerebral cortex, and amygdale (Seve et al 2004), and ZnT3 knock-out mice exhibit cognitive loss, alterations in memory and may represent a phenocopy for memory deficits of Alzheimer's disease (Adlard et al 2010;Martel et al 2010;.…”
Section: Discussionmentioning
confidence: 99%
“…The ZnT3 protein (encoded by the SLC30A3 gene) belongs to a class of proteins whose function is to lower the intracellular zinc concentrations, facilitating efflux of intracellular vesicles in the cytoplasm and/or extracellular spaces, and plays a particularly important role in neuronal zinc regulation. This protein is responsible for the accumulation of free zinc in glutamatecontaining vesicles found in the hippocampus and cortex (Gower-Winte and Levenson 2012). The SLC30A3 gene is expressed in brain regions important for cognitive development and development of different kinds of memory, such as the hippocampus, cerebral cortex, and amygdale (Seve et al 2004), and ZnT3 knock-out mice exhibit cognitive loss, alterations in memory and may represent a phenocopy for memory deficits of Alzheimer's disease (Adlard et al 2010;Martel et al 2010;.…”
Section: Discussionmentioning
confidence: 99%
“…An abundance of previous work has shown that free zinc, sequestered in synaptic vesicles, is released from neurons into the synaptic cleft where it results in postsynaptic neuronal death [2]. Although the release of synaptic zinc after injury is well accepted in the field, there have been indicators that other pools of free zinc may contribute to neuronal damage after injury.…”
Section: Potential Neurotoxic Effects Of Zinc In Traumatic Brain Injurymentioning
confidence: 99%
“…The essential trace element zinc has been implicated in many disorders of the central nervous system such as TBI, ischemia, stroke, and mood disorders including depression [2].…”
Section: Introductionmentioning
confidence: 99%
“…Zn also regulates expression of immediate early genes (e.g. c-Fos) in response to brain and behavioral activity through zinc finger transcription factors [18]. Abnormally low amounts of Zn in the brain can also induce learning and memory deficits, although results are not consistent.…”
Section: Introductionmentioning
confidence: 99%